Students’ Perception on Quizlet as a Vocabulary Learning Tool - Azizah, Sarah; Miftakh, Fauzi (Universitas Halu Oleo, 2021)
This study aims to understand how students perception Quizlet as a tool for learning English vocabulary. This researcher conducted this research at one of the junior high schools in West Cikarang, which consisted of three class VIII students. This research uses a qualitative descriptive design. In addition, the researcher collected data using interviews and questionnaires. Researchers conducted interviews via WhatsApp telephone. Questionnaires were distributed through WhatsApp groups and using a 5-point Likert scale. This study uses thematic analysis, which includes six steps. Familiarize yourself with the data and generate the initial code, search for topics, view topics, define and name data, and make a report are the six steps. The findings show that students' perceptions of using Quizlet show positive responses and feelings. Quizlet can make students feel happy and interested during learning. However, there are challenges in using Quizlet, about feeling challenged with each other during learning and the problem of internet connection that is not always stable.